Foreign direct investments and domestic investments in Romania in the economic crisis period - ZAMAN, Gheorghe; GEAMĂNU, Marinela (Annals of Spiru Haret University. Economic Series, 2010)
Investments represent one of the most important factors of the economic growth as well as of the exit from crisis and economic re-launching. The paper analyses the investments evolution (foreign and domestic) in Romania under the crisis circumstances, taking into account the main factors of influence. Based on the analysis of Romania’s investment process, in the period 2005-2010, several proposals are made aiming at the improvement of investment mechanisms and their sources of funding, including the increase in Romania’s absorption capacity of EU structural and cohesion funds in the period 2007-2013.